METHODS OF TRANSITION OF ARITHMETIC AND GEOMETRICAL MATERIALS IN AN INALIENABLE LINKAGE IN ELEMENTARY MATHEMATICS CLASSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Pupils of primary classes are also playful and during the lesson more attention is paid not to formulas, but to schemes, drawings and geometrical figures. Proceeding from their interest, in order to further increase the effectiveness of mathematics lessons, we will try to give some geometric images of some arithmetic concepts in our article.